2021
DOI: 10.3390/tropicalmed6020047
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Broiler Poultry Farms in Kathmandu Valley of Nepal: Which Antibiotics and Why?

Abstract: Inappropriate antibiotic use in food-producing animals is associated with the emergence and spread of antibiotic resistance. In industrial broiler poultry farms in three districts of Kathmandu valley, Nepal, we assessed antibiotic use prevalence, and their classes, types, and quantities. A cross-sectional questionnaire study involving field visits to large poultry farms (flock size ≥ 3000) of the Kathmandu, Bhaktapur, and Lalitpur districts was conducted. Of 30 farms (total flock size 104,200; range 3000–6000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…The strikingly high frequencies of antimicrobial usage shown in the current study could be due to knowledge differences in study populations and a generally increasing availability of antimicrobials. Also, almost all (97.0%) of the commercial poultry farms used antimicrobials, which is in agreement with studies conducted in Bangladesh (98%) [17], Nepal (90%) [18] and Nigeria (89%) [19]. The high prevalence of AMU could be attributed to administering antimicrobials for prophylaxis and growth promotion purposes.…”
Section: Discussionsupporting
confidence: 86%
“…The strikingly high frequencies of antimicrobial usage shown in the current study could be due to knowledge differences in study populations and a generally increasing availability of antimicrobials. Also, almost all (97.0%) of the commercial poultry farms used antimicrobials, which is in agreement with studies conducted in Bangladesh (98%) [17], Nepal (90%) [18] and Nigeria (89%) [19]. The high prevalence of AMU could be attributed to administering antimicrobials for prophylaxis and growth promotion purposes.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that 54%-100% of broiler and layer farms administer antibiotics from the start of the production cycle to the day they were surveyed [ 15 , 21 , 22 ]. Antibiotic usage in commercial poultry in many low- and middle-income countries including Sudan, Tanzania, Vietnam, Philippines, Pakistan, Nepal, Ghana, Nigeria and Cameroon varied from 44–100%, either at the time of farm visits or during the chicken production cycle [ 5 – 7 , 23 28 ]. For comparison, the proportion of broiler chicken farms using antimicrobials was 26% on day 1 and 49% within the first week of production in nine European countries [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although antimicrobial consumption in livestock has received little attention, an expert opinion suggests that global consumption of antimicrobials in animals is twice more than in humans (4,35). In many countries, most commercial broiler producers have reported antibiotic use, i.e., in Ghana (97%) (16), Nepal (90%) (36), Nigeria (89%) (37), Bangladesh (98%) (38), and the United States (40%) (39). Broiler farm intensification could be a driving force for the use of antibiotics as feed additives in developed countries, whereas increasing demand for poultry meat and eggs for food security could be a factor in the developing world and may lead to the risk of developing antibiotic-resistant microbes (40)(41)(42)(43).…”
Section: Current Scenario Of Antibiotic Usementioning
confidence: 99%